Heat capacity and spin susceptibility of two-dimensional t-J model: Related Topics - Antsygina, T.N.; Poltavskaya, M.I.; Poltavsky, I.I.; Chishko, K.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Thermodynamic properties of the t–J model on square and triangular lattices near half-filling are investigatedtheoretically within an analytical approach based on the Kondo and Yamaji’s Green function decouplingscheme. The temperature dependences of the heat capacity and spin susceptibility are calculated in the widetemperature range for the case when the exchange constant J is greater than the hopping amplitude t. It was found, that with the increase of doping from the half-filling, the maximum of the spin susceptibility increases and its position shifts to lower temperatures for both types of lattices. Such behavior is in agreement with the qualitative predictions [E. Dagotto, Rev. Mod. Phys. 66, 763 (1994)]. Heat capacity demonstrates a double peak shape. The high temperature peak associated with the «spin wave-like» excitations shifts to lower temperatureswith doping. The low temperature peak appears due to the holes and its height and position depend on both the doping and the ratio t/J.